Thyroid-stimulating immunoglobulin levels during low-dose antithyroid therapy predict Graves’ disease relapse - Nguyen, Phong Vu Nhat; Nguyen, Khue Thy (Frontiers in Endocrinology, 2025)
BackgroundGraves’ disease (GD) is a common autoimmune disorder often treated with antithyroid drugs (ATD), but relapse rates remain high after therapy withdrawal. This study evaluates the role of thyroid-stimulating immunoglobulin (TSI) levels in predicting relapse after ATD discontinuation in GD patients. MethodsA retrospective analysis of 349 GD patients who achieved euthyroid status on maintenance ATD therapy was conducted. TSI levels were measured using a chemiluminescent immunoassay. Of these, 88 patients discontinued ATD therapy and were monitored for relapse. Statistical analyses, including receiver operating characteristic curve analysis, were used to identify relapse predictors.ResultsThe median TSI level was significantly higher in patients who relapsed (1.63 vs. 0.52 IU/L, p<0.01), and a cutoff of 1.31 IU/L yielded 63.64% sensitivity, 78.79% specificity, and 86.67% negative predictive value. Independent relapse predictors included a TSI ≥1.31 IU/L, treatment duration of less than 18 months, and the presence of thyroid eye disease.ConclusionTSI measurement is a valuable tool for predicting relapse after ATD withdrawal in GD. A TSI cutoff of 1.31 IU/L can aid in clinical decision-making, but further prospective studies are required to confirm these findings.